2019
DOI: 10.32731/smq.281.032019.03
|View full text |Cite
|
Sign up to set email alerts
|

“No” Is Not “Low”: Improving the Assessment of Sport Team Identification

Abstract: Scholars have studied sport team identification for decades, advancing our understanding of the influence of a psychological connection to a sport team on attitudinal and behavioral outcomes. Despite the contribution of the study of team identification to the sport fan psychology and sport consumer behavior literatures, a critical issue is apparent. A review of the methods used by scholars to assess and study team identification uncovered a misinterpretation of participant responses to team identification scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…In the three decades since this work was published, myriad researchers have examined sport fan psychology and behaviour by grouping fans as either high or low in team identification (e.g., James et al, 2019;Larkin et al, 2015;Madrigal & Chen, 2008;Wann & Schrader, 1997). Implicit across these studies is the notion that team identification represents a sufficient axis on which to segment sport fans, as individuals with high levels of identification think and behave differently from others, most notably consuming with more avidity.…”
Section: Arguedmentioning
confidence: 99%
See 1 more Smart Citation
“…In the three decades since this work was published, myriad researchers have examined sport fan psychology and behaviour by grouping fans as either high or low in team identification (e.g., James et al, 2019;Larkin et al, 2015;Madrigal & Chen, 2008;Wann & Schrader, 1997). Implicit across these studies is the notion that team identification represents a sufficient axis on which to segment sport fans, as individuals with high levels of identification think and behave differently from others, most notably consuming with more avidity.…”
Section: Arguedmentioning
confidence: 99%
“…This popularity is likely a result of consumers' psychological connection with a sport team influencing a range of factors (Lock & Heere, 2017). Indeed, scholars have found that team identification can result in increased purchasing (Lee & Ferreira, 2011), more positive attitudes towards team sponsors (Chien et al, 2016), and a host of other favourable outcomes (James et al, 2019). In addition, scholars have focussed on understanding how team identification develops and is maintained (Doyle et al, 2017;Funk & James, 2001;James, 2001;Kolbe & James, 2000;Lock et al, 2009Lock et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we were also surprised that team identification as a covariate was not significant at either the ego or alter effect level. Given the popularity of team identification research in sport management (James et al, 2019;Lock & Heere, 2017), we expected individuals with higher levels of team identification to play a more focal role in the fan tie network, either through creating more outgoing fan ties or eliciting more incoming fan ties. Nevertheless, team identification did not significantly affect incoming ties nor outgoing ties for the participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we utilize team identification as the characteristic of interest within the covariate effects. Team identification is perhaps the most widely studied construct in all of sport management (James, Delia, & Wann, 2019), as scores of scholars have examined the relationship between an individual's team identification with consumption behaviors such as attendance and media consumption (Lock & Heere, 2017). Consistent with Lock and Heere's (2017) analysis of team identification, we conceptualize team identification as the part of an individual's self-concept derived from their membership in a social group (sport team) with the value and emotional significance of belonging to such group, a definition consistent with Tajfel's (1982) operationalization of social identity.…”
Section: Hypothesis Development: Covariate Effectsmentioning
confidence: 99%
“…were a fan of a sport team, the comic genre, or both, participants completed a section regarding their favorite sport team or favorite comic genre. 12 Identification with a favorite sport brand was measured using the Sport Spectator Identification Scale-Revised (SSIS-R), and a modified version was used to measure identification with the favorite comic brand (James, Delia, and Wann, 2019). 13 Next, participants reported their perceptions and behaviors toward their favorite and rival brands.…”
Section: Instrument and Participantsmentioning
confidence: 99%